Advanced electrochemical performance of Li1.95Al0.05Na2Ti6O14 anode material for lithium ion batteries. (10th September 2015) - Lao, Mengmeng; Li, Peng; Wang, Pengfei; Zheng, Xi; Wu, Weijian; Shui, Miao; Lin, Xiaoting; Long, Nengbing; Shu, Jie
Graphical abstract: Highlights: Li-site Al substitution in Li2 Na2 Ti6 O14 is reported at the first time. Al doping can improve the lithium ion diffusion in Li2 Na2 Ti6 O14 . Li1.95 Al0.05 Na2 Ti6 O14 shows enhanced electrochemical property. In-situ XRD reveals the zero-strain characteristic of Li1.95 Al0.05 Na2 Ti6 O14 . Abstract: A range of Al doped Li2 Na2 Ti6 O14 anode materials are synthesized by a simple solid state method at 800 °C. Structure and morphology investigations show that Li2-x Alx Na2 Ti6 O14 (0.0 ≤ x ≤ 0.2) are well crystallized with a particle size in the range of 100 to 300 nm, and Al doping can slightly reduce the particle size of Li2 Na2 Ti6 O14 . Electrochemical evaluation indicates that Li1.95 Al0.05 Na2 Ti6 O14 reveals the highest reversible capacity of 245.1 mAh g −1 after 40 cycles at a current density of 100 mA g −1 among all the as-prepared samples. For comparison, the reversible charge capacities for Li2 Na2 Ti6 O14, Li1.9 Al0.1 Na2 Ti6 O14, Li1.85 Al0.15 Na2 Ti6 O14 and Li1.8 Al0.2 Na2 Ti6 O14 are only 225.6, 200.0, 206.7 and 216.9 mAh g −1, respectively. Rate performance shows that Li1.95 Al0.05 Na2 Ti6 O14 also delivers the best electrochemical property with the charge capacities of 224.8 mAh g −1 at 200 mA g −1, 204.7 mAh g −1 at 300 mA g −1 and 192.4 mAh g −1 at 400 mA g −1 . The excellent electrochemical performance of Li1.95 Al0.05 Na2 Ti6 O14 is attributed to the decreased electrochemical resistance and the improved chemical diffusion coefficient induced by Al doping. Besides, the zero-strain characteristic as proved by in-situ structure analysis should also be responsible for the enhanced cycling and rate properties.